Indications and Complications of Stoma Formations in Emergency Surgery - Dincer, Mürsit; Çıtlak, Gamze (International Journal of Innovative Research in Medical Science, 2019)
Introduction: Colorectal cancers are the second leading cause of cancer death in Europe. Colonic emergencies are associated with high morbidity and mortality. The aim of this study was to discuss the ostomy indications, stoma preferences and the early stage results of these operations. Methods: The cases who underwent emergency operation were investigated retrospectively. Demographic characteristics, surgical indications, preferred type of stoma, postoperative early stage complications were analyzed. Results and Conclusion: As a result, the stoma still maintains its importance in colorectal surgery. Frequencies are preferred to minimize morbidity in emergency surgery procedures. The operations at the right time with the right indications are life-saving.